THE WAR OF GLOBAL BRANDS: THE INNOVATOR VS THE CHALLENGER - Yoga, I Made Sindhu; Patra, Nyoman Wirajaya (Universitas Pendidikan Nasional, 2019)
The purpose of this study is to explain the influence of brands and countries of origin of consumer attitudes in choosing cell phone products (iPhone and Xiaomi as a representative of two different countries). Hence, this research tries to propose and compares two different models of the brand in the correlation with the brand equity model. The data was collected from Millennial generation respondents, SES A and B who are have spending power, intention to buy and no consideration related to the price but the value of the product itself. The analysis technique used Partial Least Square (PLS). The results showed that the importance of the brand, brand performance, brand image has a positive effect on attitude. The importance of the brand, brand performance, and brand image simultaneously have a positive effect on attitude. Country of origin has a positive effect on purchase intentions. Price and attitude have a positive effect on purchase intention. Country of origin, price and attitude simultaneously have a positive effect on purchase intentions